Islam in Indonesia’s foreign policy, 1945-1949 - Fogg, K (Al-Jami'ah Research Centre, 2015)
Although most policy studies argue there has been no influence of Islam on Indonesia's foreign policy, the foreign relations of the Republic of Indonesia during the revolution for independence provide a counter-example. Because of the greater role for society in conducting, rather than just influencing, foreign relations, Islam was used as a key element in Indonesia's diplomatic efforts in the Arab world between 1945 and 1949. This led to several key, early successes for Indonesia on the world stage, but changing circumstances meant that relations with the Arab world and thus the place of Islam in foreign policy were no longer prominent from 1948.